The Correlation of External Motivation and Agency Position in The Educational Activity of Primary School Students - Tsoy L.V.; Kulagina I.Y. (Психолого-педагогические исследования)
A significant bias towards external motivation in primary school and increased requirements for the development of student’s agency has caused the relevance of the research aimed to identify the correlation of external motivation and an agency position in the educational activities of primary school students. We used recently adapted method to study educational motivation – a modification of the questionnaire "Academic Self-regulation" (SRQ-A) (T.O. Gordeeva, O.A. Sychev, M.F. Lynch, 2020), which is based on the ideas of external and internal motivation according to the theory of self-determination by E. Desi and R. Ryan. Also the following methods were used: the questionnaire "The agency position" (Yu.V. Zaretsky, V.K. Zaretsky, I.Yu. Kulagina), the projective method "Attitude to learning" (O.N. Pakhomova) and the projective method of unfinished sentences. The study involved 69 respondents (37 boys, 32 girls) – students of third and forth grades. It is shown that with the agency position, combinations of all types of educational motives are possible. At the same time, children with the agency position have higher indicators of autonomy, that is, they regulate their educational activities more independently, to a less – under the influence of external factors.